Padmini of malwa: an autobiography of Rani Ruupmati - Khayal, Priyadarshi Thakur (Daryaganj Speaking tiger, 2021)
In the pages of this book, Rani ruupmati, the Queen of Malwa, the legendary beauty men fought Wars for, narrates everything that history books leave out.
Keywords: Fiction; IAS (Batch 1970)